2023
DOI: 10.1186/s12891-023-06155-w
|View full text |Cite
|
Sign up to set email alerts
|

A first step towards a framework for interventions for individual working practice to prevent work-related musculoskeletal disorders: a scoping review

Abstract: Background Work-related musculoskeletal disorders (WMSDs) are a key topic in occupational health. In the primary prevention of these disorders, interventions to minimize exposure to work-related physical risk factors are widely advocated. Besides interventions aimed at the work organisation and the workplace, interventions are also aimed at the behaviour of workers, the so-called individual working practice (IWP). At the moment, no conceptual framework for interventions for IWP exists. This stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 122 publications
2
6
0
Order By: Relevance
“…In the topic of musculoskeletal disorders related to work, some obstacles are related to the work itself and the employer, and others, such as how to sit and stand up correctly, how to move the patient, and how to move the wheelchair, are related to the nurse, which can be led by teaching these things to promote self-efficacy in them. This finding is consistent with the results of van de Wijdeven’s ( 4 ) and Larinier et al’s studies ( 35 ). Training based on the PRECEDE-PROCEED model led to self-efficacy evaluation in nurses, and finally, the intervention improved self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the topic of musculoskeletal disorders related to work, some obstacles are related to the work itself and the employer, and others, such as how to sit and stand up correctly, how to move the patient, and how to move the wheelchair, are related to the nurse, which can be led by teaching these things to promote self-efficacy in them. This finding is consistent with the results of van de Wijdeven’s ( 4 ) and Larinier et al’s studies ( 35 ). Training based on the PRECEDE-PROCEED model led to self-efficacy evaluation in nurses, and finally, the intervention improved self-efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…These disorders cause 70 million Americans to visit medical centers annually ( 2 ), which has made them the second most important occupational disorder ( 3 ). Forty percent of all documented occurrences of musculoskeletal problems could lead to permanent disability, and these conditions account for 50% of long-term absences from work ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the reduction in moderateto-severe knee pain was greatest if floor layers started to use the new working methods before they developed knee complaints (OR 2.7 95%CI 1.02-7.26) [28,29]. These studies and the present study are also good examples that changes in the so-called 'individual working practice' by using assistive devices also contribute to a reduction in work-related musculoskeletal knee disorders [30,31]. This is important for knee osteoarthritis, given the strong, worldwide increase in this disabling disease-especially among workers-and the relatively little attention that is given to the prevention of work-related risk factors [32][33][34]; this remains important for the highly prevalent work-related lower back pain [35].…”
Section: Comparison With Other Studies and Prospectssupporting
confidence: 64%
“…This emphasizes the merits of the use of a health-impact assessment in the field of ergonomic intervention studies to prevent work-related musculoskeletal disorders, as was performed in the present study. Given the numerous studies performed on physical exposure assessments in ergonomics to prevent these work-related musculoskeletal disorders [30], we suggest that researchers and practitioners consider including a simple health-impact assessment to estimate the potential health benefits-in terms of a musculoskeletal disease or disorder-of preventive ergonomic measures more often.…”
Section: Comparison With Other Studies and Prospectsmentioning
confidence: 99%
“…Demographic questions, covering age, height, weight, educational status, marital status, work experience, physical activity status, dairy consumption status, and financial status. When choosing the demographic variables for this research, we took into account factors that have previously been identified as potential influencers of musculoskeletal disorders and ergonomic practices which supported by pertinent literature [ 2 , 8 , 12 , 31 , 32 ]. Participants’ income levels were classified as ‘well,‘ ‘moderate,‘ or ‘poor,‘ based on their subjective evaluation of their financial well-being obtained through the questionnaire.…”
Section: Methodsmentioning
confidence: 99%